Association Between Smoking and Pain, Functional Disability, Anxiety and Depression in Patients With Chronic Low Back Pain - Qi-Hao Yang; Yong-Hui Zhang; Shu-Hao Du; Yu-Chen Wang; Xue-Qiang Wang; Xue-Qiang Wang (Frontiers Media S.A., 2023)
Objectives: Chronic low back pain (CLBP) accounts for a majority of the disability associated with LBP, which can produce long-term negative effects. This cross-sectional study aimed to investigate the association between smoking and pain, dysfunction and psychological status in patients with CLBP.Methods: The 54 patients with CLBP were recruited and divided into smoking and non-smoking groups. Their pain, dysfunction, anxiety, depression, fear and quality of life were evaluated. The amount of cigarettes smoked daily was recorded.Results: Significant differences in VAS, ODI, RMDQ and FABQ and the impact of LBP on life and work were found between smoking and non-smoking patients. In addition, a correlation was found between the daily cigarette smoking amount and VASmax, FABQtotal, SDS and FABQ-W. Moreover, a correlation was observed between the amount of cigarettes smoked daily and the degree of impact of low back pain on work.Conclusion: The study found that smoking affected the aggravation of symptoms in patients with CLBP, which indicated that patients with CLBP and people at risk of LBP should be aware of the harm caused by smoking.